2009
DOI: 10.1007/s10147-008-0806-y
|View full text |Cite
|
Sign up to set email alerts
|

An atypical extrahepatic metastasis of the distal phalanx from hepatocellular carcinoma

Abstract: A 49-year-old woman presented with severe swelling and pain of the left little finger, which had exacerbated rapidly, in October 2006. The patient had a history of hepatocellular carcinoma and metastatic lung cancer. She had undergone partial hepatectomy for the hepatocellular carcinoma in September 2001 and pulmonary resection for metastatic lung cancer in November 2005. Roentgenogram of the hand on admission showed complete destruction of the distal phalanx of the left little finger. The final pathological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…This is one of the rare instances of bony metastatic HCC. Munk et al demonstrated metastasis in HCC to sacrum and gluteus muscles while Matsunaga et al found extrahepatic metastasis to the distal phalanx of a finger [12] Darzi et al demonstrated abdominal wall metastasis following HCC after laparoscopy [13]. Alpha fetoprotein (AFP) usually correlates with tumor size and doubling time of AFP correlates with the tumor doubling time.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the rare instances of bony metastatic HCC. Munk et al demonstrated metastasis in HCC to sacrum and gluteus muscles while Matsunaga et al found extrahepatic metastasis to the distal phalanx of a finger [12] Darzi et al demonstrated abdominal wall metastasis following HCC after laparoscopy [13]. Alpha fetoprotein (AFP) usually correlates with tumor size and doubling time of AFP correlates with the tumor doubling time.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, bone metastasis of hepatocellular carcinoma to the hand is extremely rare. To our knowledge, only five cases have been reported in the literature (7)(8)(9)(10)(11). We report the case of 60-year-old patient with metastatic hepatocellular carcinoma of the distal phalanx of the right 4…”
Section: Introductionmentioning
confidence: 99%